Learning from the diversity of national structures, processes and intentions with regard to extended education - Krepper, Bettina; Efstathiades, Alexandra; Loparics, James (Frontiers in Education, 2025)
IntroductionIn European countries, the emphasis placed on Extended Education (EE) differs not only in practice but also in policies and literature. In fact, there are still no standardized concepts or definitions of this specific educational area.MethodsThe aim of this study is to contribute to a transnational understanding of EE by inductive content analysis of essential documents from five different countries. The results of this study will facilitate a better understanding of shared factors which can be used to improve student access, success and retention in education, generate valuable guidelines for effective leadership and highlight the potentials of public governance for social innovation. As part of the Erasmus+ project “EKCO” (Extended Education Facilitating Key Competences through Cooperative Learning), a research team consisting of local experts in the field of EE from Norway, Sweden, Denmark, Switzerland and Austria was asked to provide a selection of local literature on EE that they considered particularly relevant. A total of 19 documents were submitted from the five countries. In the present study, the expert sampling was subjected to an inductive content analysis using MAXQDA software to identify the salient points that emerged from the sampling.ResultsThe results indicate that five main categories can be identified in the EE literature offered, namely: (1). Factors influencing EE, (2). Institutions and structure, (3). Pedagogical requirements, (4). Content of EE and (5). Factors influenced by EE.DiscussionThe analysis of the data shows that, despite national differences, there are common intentions, processes and structures that are productive for the development of key competences and future skills. Moreover, the interplay of these factors should be considered when discussing EE. The article discusses how national EE policies can learn from the diversity of their structures, processes and intentions.